2012
DOI: 10.1155/2012/894708
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation of a NewS-Methyl Benzothioate Compound from a Marine-DerivedStreptomycessp.

Abstract: The application of an HPLC bioactivity profiling/microtiter plate technique in conjunction with microprobe NMR instrumentation and access to the AntiMarin database has led to the isolation of a new 1. In this example, 1 was isolated from a cytotoxic fraction of an extract obtained from marine-derived Streptomyces sp. cultured on Starch Casein Agar (SCA) medium. The 1D and 2D 1H NMR and ESIMS data obtained from 20 μg of compound 1 fully defined the structure. The known 2 was also isolated and readily dereplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Streptomyces are widely distributed in global marine ecosystems, such as marine sediments and seawater, marine animals and algae (Blunt et al 2013). Streptomyces have been isolated from six kinds of ascidians (Aplidium lenticulum, Didemnum sp., E. turbinata, Molgula manhattensis, Styela canopus and Styela clava) (Chen et al 2018b), and some compounds have been isolated from ascidian-derived Streptomyces, such as polyketides (bisanthraquinones 1-2, griseorhodin A, germicidin), alkaloids (piericidin C7, C8, A1, A2, bohemamine, etc) and other compounds (Li and Piel 2002;Socha et al 2006;Hayakawa et al 2007;Mahyudin et al 2012;Pei et al 2017;Chen et al 2018b). Among the 135 strains with antimicrobial activity, 39 strains (28Á89%) belonged to the genus Streptomyces in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Streptomyces are widely distributed in global marine ecosystems, such as marine sediments and seawater, marine animals and algae (Blunt et al 2013). Streptomyces have been isolated from six kinds of ascidians (Aplidium lenticulum, Didemnum sp., E. turbinata, Molgula manhattensis, Styela canopus and Styela clava) (Chen et al 2018b), and some compounds have been isolated from ascidian-derived Streptomyces, such as polyketides (bisanthraquinones 1-2, griseorhodin A, germicidin), alkaloids (piericidin C7, C8, A1, A2, bohemamine, etc) and other compounds (Li and Piel 2002;Socha et al 2006;Hayakawa et al 2007;Mahyudin et al 2012;Pei et al 2017;Chen et al 2018b). Among the 135 strains with antimicrobial activity, 39 strains (28Á89%) belonged to the genus Streptomyces in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This phenazine has antimicrobial activity against Vibrio anguillarum and Vibrio parahaemolyticus , lethal activity against Artemia salina , and enzyme inhibiting activity against Alpha-glucosidase [ 53 ]. Bohemamine ( 85 ) was isolated from Streptomyces sp., a bacterial associated with an unidentified ascidian collected from Lyttelton Harbor, New Zealand [ 115 ]. Four known diketopiperazine alkaloids, cyclo (6-OH- d -Pro- l -Phe) ( 86 ), bacillusamide B ( 87 ), cyclo ( l -Pro- l -Leu) ( 88 ) and cyclo ( l -Pro- l -Ile) ( 89 ), were isolated from actinobacteria Streptomyces sp.…”
Section: Structure and Bioactivities Of Natural Productsmentioning
confidence: 99%
“…without biological evaluation. 12 Hexasubstituted benzothioates are rarely found from sources other than actinobacteria, with the only examples being mortivinactin B from the fungus Mortierella vinacea 13 and polycarpamine B from the marine ascidian Polycarpa auzata. 14 Using a cell-based assay to evaluate antidiabetic compounds, we observed that suncheonosides A−D (1−4, respectively) increased the production of adiponectin during adipogenesis in human bone marrow mesenchymal stem cells (hBM-MSCs).…”
Section: Journal Of Natural Productsmentioning
confidence: 99%